A Novel Strategy to Overcome the Hurdle for Commercial All‐Solid‐State Batteries via Low‐Cost Synthesis of Sulfide Solid Electrolytes (Small Methods 11/2021). Issue 11 (12th November 2021) - Kim, Min‐Ju; Choi, Ik‐Hyeon; Jo, Seong Chan; Kim, Byung Gon; Ha, Yoon‐Cheol; Lee, Sang‐Min; Kang, Sung; Baeg, Kang‐Jun; Park, Jun‐Woo
Abstract : Back Cover In article number 2100793, Baeg, Park and co‐workers develop a novel pathway for the solution‐phase synthesis of sulfide solid electrolytes with ionic conductivities as high as 1.8 mS cm −1 . This study offers a promising solution for overcoming the hurdle of production cost of the final all‐solid‐state batteries to realize commercial rechargeable batteries with high energy density and stability that can replace the current lithium‐ion batteries.